Alternate Universe of the Same Place: An Interview with Jo-Anne Elder. (June 2018) - Neilson, Shane
Abstract : Jo-Anne Elder is a leading Canadian translator of Québécois and Acadian French poetry into English. Conducted by email and in person over the Spring and Summer of 2017, this interview uses Tony Tremblay's ideas about intercultural work in New Brunswick as a frame to examine Elder's work with French writers within and outside the province. Writers considered in the interview include Herménégilde Chiasson, Fred Cogswell, and Serge Patrice Thibodeau. The interview also covers Elder's experience as editor of ellipse and concludes by considering the part spirituality plays in the act of translation.